Evaluation of MEDI8852, an Anti-Influenza A Monoclonal Antibody, in Treating Acute Uncomplicated Influenza - Ali, S. Omar (Antimicrob Agents Chemother, 2018)
We evaluated MEDI8852, a human IgG1 monoclonal antibody that binds a highly conserved influenza A hemagglutinin stalk epitope, in outpatients with uncomplicated influenza A infection. A total of 126 subjects aged 18 to 65 years were enrolled during the 2015 to 2016 Northern and 2016 Southern Hemisphere seasons. Subjects with symptom onset ≤5 days before dosing were randomized to four cohorts: 750 mg (cohort 1) or 3,000 mg (cohort 2) MEDI8852 (single intravenous infusion) plus 75 mg oseltamivir, placebo plus 75 mg oseltamivir (cohort 3), and 3,000 mg MEDI8852 alone (cohort 4). Subjects were monitored through day 10 for solicited influenza symptoms, day 28 for adverse events (AEs), and day 101 for serious AEs and AEs of special interest. Nasopharyngeal samples were collected through day 7 for confirmation of influenza A infection, viral shedding, and oseltamivir and MEDI8852 susceptibility. Slightly more AEs were reported in subjects receiving MEDI8852 (cohorts 1, 2, and 4 combined: 39/93, 41.9%) than oseltamivir only (cohort 3: 10/32, 31.3%). Most AEs were mild or moderate. The most common AE was bronchitis (11/93, 11.8%; 1/32, 3.1%). The median (range) decrease in viral shedding (log(10) virus genome copies/ml) was similar between the two groups (−3.58 [−6.2. 0.5]; −3.43 [−5.9, 0.9]). Genotypic analyses found a limited number of hemagglutinin and neuraminidase amino acid changes between viruses isolated before and after therapy; however, none appeared within a known oseltamivir-resistant site or MEDI8852-binding region. The safety profile of MEDI8852 supports its continued development for treatment of patients hospitalized with influenza A infection. (This study has been registered at ClinicalTrials.gov under identifier NCT02603952.)